Gravitational rainbow of massive particles - Accioly, A. (World Scientific Publ Co Pte Ltd, 2002)
Photon propagation is non-dispersive within the context of semiclassical general relativity. What about the remaining massless particles? It can be shown that at the tree level the scattering of massless particles of spin 0, 1/2, 1 or whatever by a static gravitational field generated by a localized source such as the Sun, treated as an external field, is non-dispersive as well. It is amazing, however, that massive particles, regardless of whether they have integral or half-integral spin, experience an energy-dependent gravitational deflection. Therefore, semiclassical general relativity and gravitational rainbows of massive particles can coexist without conflict. We address this issue in this essay.